RELATIONSHIP BETWEEN BLOOD PRESSURE DURING DAY OF ADMITTANCE AND CLINICAL OUTCOME SCALE (GADJAH MADA STROKE SCALE) FOR STROKE PATIENT AFTER FIVE DAY - , FARHAH BINTI ADNAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Almost 80% of patient with acute stroke will have an acute hypertensive response. However, management for hypertension remains controversial. Data from observational study have suggested that high blood pressure is related to poor outcome, whereas blood pressure elevation during the acute phase might help to maintain cerebral perfusion. Objectives : The main objective of the study is to determine if the blood pressure level during stroke attack affect the clinical outcome of the patient. Method : This research will be conducted using Observational Descriptive Analysis Study design. All the data will be obtained from secondary data which is the medical record in RSUP Dr. Sardjito. The medical record will be of the ischemic stroke patients who are admitted in RSUP Dr. Sardjito from January 2012 to December 2012. The data obtained is of the blood pressure level of the patient during admittance and his or her clinical outcome in the form of Gadjah Mada Stroke Scale after five days The data analysis was done in January 2014 using IBM SPSS 20. Result :the systolic blood pressure and the mean arterial pressure is not significant TO GMSS score (r = 0.090,r=- 0.17, pâ¥0.05).the diastolic blood pressure has a significant weak correlation to GMSS (r =0.257,Pâ¤O.O5) Conclusion: As a conclusion, the results show that there are a weak positive correlation between diastolic blood pressure and Gadjah Mada Stroke Scale. This means that when the siastolic blood pressure increases the patients has better clinical outcome. Although the systolic and mean arterial pressure show correlation to GMSS, the correlation is not significant and may be due to chance.